1973
DOI: 10.1063/1.1662871
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of gold particles to silicon and gold substrates in ultrahigh vacuum

Abstract: A variable-temperature ultrahigh vacuum scanning tunneling microscope Rev. Sci. Instrum. 72, 2613 (2001 10.1063/1.1372165 Design and performance of an ultrahigh vacuum system for metallic multilayers By use of an ultracentrifuge, the force of adhesion between small gold spheres (2~8 !L in diameter) and the following types of substrates has been measured: (III) cleavage planes of silicon single crystals with or without a chemisorbed oxygen monolayer and, alternatively, cleavage planes covered with oxide laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The adhesion between Au and Si or SiO 2 is known to be rather poor [1820]. Böhme et al [21] demonstrated that the oxygen layer forming on the silicon substrates affects the adhesion between Au particles and silicon substrates. Furthermore, Langbein et al stated that the vdW attraction between two surfaces is only affected by their outer layers, if the separation of the surfaces is lower or in the same range as the thickness of the outer layer [22].…”
Section: Introductionmentioning
confidence: 99%
“…The adhesion between Au and Si or SiO 2 is known to be rather poor [1820]. Böhme et al [21] demonstrated that the oxygen layer forming on the silicon substrates affects the adhesion between Au particles and silicon substrates. Furthermore, Langbein et al stated that the vdW attraction between two surfaces is only affected by their outer layers, if the separation of the surfaces is lower or in the same range as the thickness of the outer layer [22].…”
Section: Introductionmentioning
confidence: 99%
“…In rare cases where some residual particles remained after these two steps, a brief sonication in basic 10% EDTA was also used to ensure surfaces were free from NPs. Generally, gold shows stronger adhesion to mica substrates, while glass and silica surfaces often require an adhesion layer of Cr or Ti to bridge the mismatch between the surface energies of Au and SiO 2 . In this work, we have not used an adhesion layer on any of the substrates and the resulting metallic microfeatures withstood short sonication times.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, gold shows stronger adhesion to mica substrates, while glass and silica surfaces often require an adhesion layer of Cr or Ti to bridge the mismatch between the surface energies of Au and SiO 2 . 84 In this work, we have not used an adhesion layer on any of the substrates and the resulting metallic microfeatures withstood short sonication times. This indicates that the gold patterns adhere reasonably well on substrates tested.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…First, a Si/SiO 2 substrate (375 μm thick) is prepared with lithographically defined Cr(5 nm)/Au(55 nm) contact pads via direct current sputtering. The chromium is employed as an adhesion layer, since the direct growth of gold on Si/SiO 2 shows poor adhesion [54]. Subsequently the sample is spin-coated with a thick methyl methacrylate (MMA) and polymethyl methacrylate (PMMA) double resist layer which is required to produce a shadow-mask.…”
Section: Methodsmentioning
confidence: 99%